PATTERNS OF FRUIT AND VEGETABLE CONSUMPTION AND PHYSICAL ACTIVITY IN PREVENTING HYPERTENSION IN ADOLESCENTS SURABAYA: A QUALITATIVE STUDY - Alberta, Lembunai Tat Alberta; Widyastuti, Dwi Utari; Ragayasa, Adivtian (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Hypertension is a health problem in the world because it is the main cause of cardiovascular disease and the number one cause of death in the world every year. Research shows hypertension can occur in the adolescent age group and its prevalence continues to increase which is the cause of hypertension in adults and the elderly. The high prevalence of hypertension in adolescents is not only caused by genetic but also behavioral factors, including lack of consumption of fruits, vegetables and physical activity. This condition shows that there is still low consumption of vegetables and fruits as well as physical activity in adolescents so that they are at risk of suffering from hypertension in adulthood. Objectives: To explore the consumption patterns of fruits, vegetables, and physical activity to prevent hypertension in students majoring in nursing at the Sutomo Surabaya campus. Methods: Qualitative research method with phenomenological approach Data collection was carried out directly using in-depth interview method. Data analysis using content analysis and thematic analysis techniques. Results: The results showed that students only consume certain types of fruits and processed vegetable forms, not all students consume vegetables and fruits every day and think that vegetables and fruits are useful for digestion, prevent various diseases including hypertension, maintain stamina and are fun foods. Most students like easy and light physical activity, although they rarely do it because of the busy work of college. Students think that physical activity is beneficial for preventing hypertension and obesity, forming a good physique and heart health, for fitness, skin health and the immune system. Conclusion: Students majoring in nursing at the Sutomo campus have not maximally applied the pattern of consumption of vegetables and fruits, physical activity even though they already know the benefits in preventing hypertension.